Assessment of Factors Influencing Tendency of Auditors to Use Achievments of Information Technology: The Independent Auditors' perspective - Gholam Hossian Mahdavi (Shahid Bahonar University of Kerman, 2014)
This research investigates the factors influencing auditors’ tendency for the use of information technology achievements, regarding independent auditors' view point in the group of auditor members of the Iranian association of certified public accountants. In this respect, seven hypotheses have been developed and tested, using questionnaire. The results of statistical tests of the research hypotheses showed that points of view of the auditors, who are the members of the Iranian association of certified public accountants, take account of the achievements of information technology to increase the efficiency of auditing. Also, the auditors believe senior managers’ view points, auditors’ risk preferences, budgetary pressures, perceived usefulness of the achievements of information technology and perceived ease of use are the factors that influence the tendency of auditors to use achievements of information technology. Furthermore, according to the research results, except for sex, all of the personal characteristics of auditors, for example professional work experience, field of study, academic degree and age have meaningfull influence on the independent auditors' point of view about effective factors determining achievements of information technology.